2020
DOI: 10.3390/jcm9123945
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Pancreatectomy for Isolated Local Recurrence in the Remnant Pancreas Following Radical Pancreatectomy for Pancreatic Ductal Adenocarcinoma: A Pooled Analysis

Abstract: The mainstream treatment for recurrent pancreatic cancer is potent chemotherapy or chemoradiotherapy. However, recent clinical investigations have suggested a potential oncologic role of local resection of recurrent pancreatic cancer. This systemic review with a pooled analysis aimed to assess the potential role of local repeated pancreatectomy with respect to the survival outcomes for patients with recurrent pancreatic ductal adenocarcinoma (PDAC) in the remnant pancreas. The PubMed database was searched, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Yamada et al reported a median survival of 26 months in patients with remnant pancreatic recurrence who underwent resection [27] . Considering the long interval from initial pancreatectomy to the diagnosis of remnant pancreatic cancer, it is quite difficult to distinguish metachronous remnant pancreatic recurrence from a second primary pancreatic cancer [27] , [28] , [29] . We present a case of PASC in a patient who developed remnant pancreatic cancer 5 years after successful distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al reported a median survival of 26 months in patients with remnant pancreatic recurrence who underwent resection [27] . Considering the long interval from initial pancreatectomy to the diagnosis of remnant pancreatic cancer, it is quite difficult to distinguish metachronous remnant pancreatic recurrence from a second primary pancreatic cancer [27] , [28] , [29] . We present a case of PASC in a patient who developed remnant pancreatic cancer 5 years after successful distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of recurrence in RP was only 3.9% 45 . A recent pooled analysis reported that repeated pancreatectomy cannot completely replace the role of adjuvant chemotherapy but should be considered for cases with isolated local recurrent PDAC in the RP 46 . Recently, a prospective observation report evaluated recurrences of early‐stage PDAC diagnoses, including 16 with stage 0 and 14 with stage IA.…”
Section: Endoscopic Approach For Early‐stage Pdac In Rpmentioning
confidence: 99%
“…45 A recent pooled analysis reported that repeated pancreatectomy cannot completely replace the role of adjuvant chemotherapy but should be considered for cases with isolated local recurrent PDAC in the RP. 46 Recently, a prospective observation report evaluated recurrences of early-stage PDAC diagnoses, including 16 with stage 0 and 14 with stage IA. Of these 30 cases, nine demonstrated a recurrence of PDAC after initial surgery; two had been diagnosed as stage 0 and seven as stage IA.…”
Section: Endoscopic Approach For Early-stage Pdac In Rpmentioning
confidence: 99%
“…This Special Issue of the Journal of Clinical Medicine , entitled “Recent Advances in Pancreatic Neoplasms”, focuses on new possible strategies to treat pancreatic neoplasms, especially pancreatic adenocarcinoma (PDCA). This Special Issue contains 13 articles, 11 studies and 2 review articles, focusing on the pancreatic ductal adenocarcinoma ( n = 10), intraductal papillary mucinous neoplasm (IPMN) ( n = 1), neuroendocrine tumors ( n = 1) and secondary tumor to the pancreas ( n = 1) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Seven papers [ 4 , 5 , 6 , 9 , 10 , 11 , 14 ] explored new prognostic factors potentially able to stratify patients with pancreatic cancer and different survival rates in order to select the adequate treatment.…”
mentioning
confidence: 99%
“…Despite the fact that surgery for recurrent cancer is not recommended and rarely feasible, a series of patients with recurrent pancreatic cancer who underwent re-resection were increasingly reported in the English literature. Choi et al [ 15 ] from Korea, reviewed the literature to assess the role of repeated pancreatectomy for patients with recurrent pancreatic cancer in the remnant pancreas. The median overall survival was 60 months after repeated pancreatectomy for isolated local recurrence.…”
mentioning
confidence: 99%